Peningkatan Penyelenggaraan SLTP Keterampilan - Supriyoko Supriyoko (Universitas Negeri Malang, 2016)
Many junior secondary dropouts and many junior secondary graduates who do not go to senior secondary school create a lot of young people who are unprepared to join the work force. Yet it is against the reguation to establish junior secondary school. The problem is solved by establishing skill oriented junior secondary school. Though still semi-skilled their graduates could easily join the work force. There are minor legal problem for the establishment of such kind of school, but this problem rests more in legal interpretation rather than their material. Some additional ministerial decress could solve this problem.